Elective versus non-elective caesarean sections: A multinomial regression analysis of predictors and foetal outcome in a Tertiary Health Facility in Southwestern Nigeria - Adebayo Akadri; Akinmde Adepoju; Elizabeth Grillo; Omobolanle Akadri (Babcock University Medical Journal, 2025)
Objective: This study assessed the demographic and obstetric predictors of elective and non-elective caesarean section and the fetal outcomes at Babcock University Teaching Hospital (BUTH).